Severe Persistent Bronchial Asthma: Literature Review - Maryam Iribaram, Siti; Pratiwi, Ulfa Ayu; Arifah, Adila Nur; Aebi, Nur; Nur Azizah, Sepriani; Ayu Wulandari, Dinda; Fadillah, Khusnul; Almaida Banda, Dhija; Purnamasari, Anisa; Veronica, Alda Aprilia (Nursing Genius Journal, 2025)
Background: Severe persistent asthma is the most complex form of asthma, characterized by symptoms that cannot be optimally controlled despite the administration of high-dose standard therapy such as inhaled corticosteroids (ICS) combined with long-acting beta-2 agonists (LABA) and/or oral corticosteroids. This type of asthma significantly impacts the patient’s quality of life, increases the frequency of exacerbations, and leads to higher healthcare costs. Purpose: To evaluate the impact of combination therapy and biological therapy approaches on key clinical outcomes such as reduction in exacerbations, improvement in quality of life, and decreased use of systemic corticosteroids. Methods: Articles were collected from the PubMed, ScienceDirect, and other peer-reviewed journal databases, with a publication range from 2021 to 2025. Results: The search yielded 10 articles that met the specified criteria and keywords. Biologic therapy has been proven effective in reducing exacerbations, improving lung function, and decreasing dependence on systemic corticosteroids. Conclusion: The importance of early intervention, accurate diagnostic approaches, and careful use of biologic therapy highlights the need for timely detection and treatment to prevent long-term damage.